THE RELEVANCE OF STOICISM PHILOSOPHY TO THE SOCIAL AND RELIGIOUS LIFE OF GENERATION Z - Farrah Ananta Erva Zabryna; Irzum Farihah (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
The development of all-digital technology has made Generation Z have a pattern of thought that tends to be unique and creative in terms of socializing and thinking. This uniqueness tends to be followed by the amount of information on the timeline that can be accessed through any platform. This affects how Generation Z acts in their social and religious lives. The influence of this information can lead to perceptions resulting from their thinking in processing an event. This research aims to find the relationship between the teachings of stoicism and Generation Z’s social and religious life in creating a wiser life and the ability for self-control. Generation Z’s social and religious life cannot be separated from digital advances that can influence their religious mindset. Meanwhile, the philosophy of stoicism is a form of teaching self-control through rational thinking behavior. This research uses qualitative methods with data collection through interviews and observations. In-depth interviews were conducted with Generation Z who have known the concept of stoicism in the age range of 18–23 years old and live in Kudus City. Secondary data was obtained through various journals related to the topic. The results of this study show that in carrying out social and religious life, Generation Z has been able to understand how to act properly without involving emotions and trying to think rationally. Furthermore, Generation Z can accustom themselves to doing spiritual activities in religion both personally and in groups, to provide religious awareness through self-control of the development of negative emotions. This is because there are similar indicators to achieve happiness in religious teachings and philosophy. In religion, the Qur’an is prioritized as the word of God with the main function of showing humans the essence of truth, while philosophy uses rationality as a tool to find truth without being bound by emotional factors. It can be concluded that the Qur’an and the philosophy of stoicism have the same concept related to gratitude and patience.